Alkaline phosphatase grafting on bioactive glasses and glass ceramics - Verné, Enrica; Ferraris, Sara; Vitale-Brovarone, Chiara; Spriano, Silvia; Bianchi, Claudia L.; Naldoni, Alberto; Morra, Marco; Cassinelli, Clara (Acta biomaterialia, 2010)
Bone integration of orthopaedic or dental implants and regeneration of damaged bone at the surgical site are still unresolved problems in prosthetic surgery. For this reason, biomimetic surfaces (i.e. both inorganic and biological bioactive surfaces) represent a challenge for bone implantation. In this research work a hydrolase enzyme (alkaline phosphatase) was covalently grafted to inorganic bioactive glass and glass ceramic surfaces, in order to impart biological bioactivity. The functionalized samples were analysed by means of X-ray photoelectron spectroscopy in order to verify enzyme presence on the surface. Enzyme activity was measured by means of UV–visual spectroscopy after reaction with the natural substrate. Scanning electron microscopy–energy-dispersive spectroscopy observations allowed monitoring of the morphological and chemical modification of the materials during the different steps of functionalization. In vitro inorganic bioactivity was investigated by soaking samples in simulated body fluid. Enzymatic activity of the samples was tested and compared before and after soaking. Enzymatic activity of the solution was monitored at different experimental times. This study demonstrates that alkaline phosphatase could be successfully grafted onto different bioactive surfaces while maintaining its activity. Presence of the enzyme in vitro enhances the inorganic bioactivity of the materials tested.